Adubações crescentes, teores nutricionais e caracteres agronômicos das culturas de girassol e trigo - Cunha, Letícia do Socorro (2024)
The objective of this work was to evaluate the agronomic characteristics and nutritional contents, in response to increasing doses of NPK in top dressing, in two experiments, in the Eutroferric Red Latosol. For each harvest, three experiments were carried out in a randomized block design, with four replications and five treatments, in coverage. In the first, second and third, five doses of N, P and K were evaluated (0, 25, 50, 100 and 200 kg ha-1), supplied via fertilizers (urea used as a source of N, super phosphate simple for P2O5 and potassium chloride to supply K2O), totaling 20 experimental units. Assessments of agronomic traits were carried out, such as: initial and final stand; number of achene per chapter; chapter diameter; Mass of 1000 achenes; plant height; productivity and nutritional content of soil and leaf tissue. For the sunflower crop in the 2020/21 harvest, fertilization with N and P2O5 proved effective, however, it showed greater height at a dose of 200 kg ha-1, with an average of 141 cm per plant referring to the treatment with P2O5 fertilizer. Productivity had a positive increase for fertilization with N and K2O, both at a dose of 200 kg ha-1. In the 2021/22 harvest, the height of sunflower plants was also favored by doses of N and P2O5, corroborating the previous harvest. Productivity resulted in significant gains with nitrogen and potassium fertilization. For the wheat crop, in the 2021/22 harvest, the number of spikelets per ear with N and P fertilization proved to be effective, however, it showed greater height at doses of 100 and 200 kg ha-1, with an average of 17 spikelets per ear, referring to the treatment with P fertilization. The number of grains per ear was favored by nitrogen fertilization. Productivity increased positively with N fertilization at a dose of 100 kg ha-1. In the 2022/23 harvest, there was no significant effect on the studied agronomic traits of wheat. In the 2021/22 harvest, regarding the nutritional content of sunflower, there was no significant effect for each element in the three experiments and for the variables studied, in responses to fertilization with N, P2O5 and K2O in top dressing. In the 2022/23 harvest, there were significant results for the nutritional contents related to the soil, in the experiment of P (42 mg dm-3) and K (1.20 cmolc dm-3) for doses of 200 and 50 kg ha-1 in sunflower cultivation. In both the 2021/22 and 2022/23 harvests, the nutritional contents of the wheat crop related to soil and leaf analysis did not show a significant response in the N, P2O5 and K2O experiments, respectively in coverage, under conditions of a Eutroferric Red Latosol from Marechal Cândido Rondon-PR.